K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

10 tháng 10 2019

(x2 +1)(x-3)-(x-3)(x2 +3x+9)

=x3 -3x2 +x-3-[(x-3)(x2 +3x+9)]

=x3 -3x2 +x-3-[x3+3x2 +9x-3x-9x-27]

=x3 -3x2 +x-3-x3 -3x2 -9x+3x2 +9x+27

=(x3 -x3)+(-3x2 -3x2 +3x2)+(x-9x+9x)+(-3+27)

=-3x2 +x+24

5 tháng 10 2020

a) \(\left(x+3\right)^2-\left(x-4\right)\left(x+8\right)=1\)

\(\Leftrightarrow\left(x^2+6x+9\right)-\left(x^2+4x-32\right)-1=0\)

\(\Leftrightarrow2x=-40\)

\(\Rightarrow x=-20\)

b) \(\left(x+3\right)\left(x^2-3x+9\right)-x\left(x-2\right)\left(x+2\right)=15\)

\(\Leftrightarrow x^3+27-x^3+4x=15\)

\(\Leftrightarrow4x=-12\)

\(\Rightarrow x=-3\)

c) \(\left(x-2\right)^2-\left(x+3\right)^2-4\left(x+1\right)=5\)

\(\Leftrightarrow\left(x^2-4x+4\right)-\left(x^2+6x+9\right)-\left(4x+4\right)=5\)

\(\Leftrightarrow-14x=14\)

\(\Rightarrow x=-1\)

5 tháng 10 2020

d) \(\left(2x-3\right)\left(2x+3\right)-\left(x-1\right)^2-3x\left(x-5\right)=-44\)

\(\Leftrightarrow4x^2-9-\left(x^2-2x+1\right)-\left(3x^2-15x\right)=-44\)

\(\Leftrightarrow17x=-34\)

\(\Rightarrow x=-2\)

e) \(\left(x-2\right)^3-\left(x-3\right)\left(x^2+3x+9\right)+6\left(x+1\right)^2=49\)

\(\Leftrightarrow x^3-6x^2+12x-8-x^3+27+6x^2+12x+6=49\)

\(\Leftrightarrow24x=24\)

\(\Rightarrow x=1\)

VC
26 tháng 7 2021

\(a,\left(x-3\right)\left(x^2+3x+9\right)-\left(x^2-1\right)\left(x+27\right)\)

\(=\left(x^3-27\right)-x^3-27x^2+x+27=x-27x^2\)

\(b,\left(3-x\right)^3-\left(x+3\right)\left(x^2-3x+9\right)\)

\(=27-9x+3x^2-x^3-\left(x^3+27\right)=3x^2-9x-2x^3\)

\(c,\left(x-2\right)\left(x^2+2x+4\right)-x\left(x-3\right)\left(x+3\right)\)

\(=\left(x^3-8\right)-x\left(x^2-9\right)=x^3-8-x^3+9x=9x-8\)

26 tháng 7 2021

a) (x-3)(x2+3x+9)-(x2-1)(x+27)

=(x3-27)-(x3+27x2-x-27)

=x3-27-x3-27x2+x+27

=-27x2+x

=x(-27x+1)

b) (3-x)3-(x+3)(x2-3x+9)

=27-27x+9x2-x3-x3-27

=-2x3+9x2-27x

=x(-2x+9x-27)

c) (x-2)(x2+2x+4)-x(x-3)(x+3)

=x3-8-x(x2-9)

=x3-8-x3+9x

=9x-8

#H

5 tháng 10 2020

a) ( 5x - y )( 25x2 + 5xy + y2 ) = ( 5x )3 - y3 = 125x3 - y3

b) ( x - 3 )( x2 + 3x + 9 ) - ( 54 + x3 ) = x3 - 33 - 54 - x3 = -27 - 54 = -81

c) ( 2x + y )( 4x2 - 2xy + y2 ) - ( 2x - y )( 4x2 + 2xy + y2 ) = ( 2x )3 + y3 - [ ( 2x )3 - y3 ]= 8x3 + y3 - 8x3 + y3 = 2y3

d) ( x + y )2 + ( x - y )2 + ( x + y )( x - y ) - 3x2 = x2 + 2xy + y2 + x2 - 2xy + y2 + x2 - y2 - 3x2 = y2

e) ( x - 3 )3 - ( x - 3 )( x2 + 3x + 9 ) + 6( x + 1 )2

= x3 - 9x2 + 27x - 27 - ( x3 - 33 ) + 6( x2 + 2x + 1 )

= x3 - 9x2 + 27x - 27 - x3 + 27 + 6x2 + 12x + 6

= -3x2 + 39x + 6

= -3( x2 - 13x - 2 )

f) ( x + y )( x2 - xy + y2 ) + ( x - y )( x2 + xy + y2 ) - 2x3

= x3 + y3 + x3 - y3 - 2x3

= 0

g) x2 + 2x( y + 1 ) + y2 + 2y + 1

= x2 + 2x( y + 1 ) + ( y2 + 2y + 1 )

= x2 + 2x( y + 1 ) + ( y + 1 )2

= ( x + y + 1 )2

= [ ( x + y ) + 1 ]2

= ( x + y )2 + 2( x + y ) + 1

= x2 + 2xy + y2 + 2x + 2y + 1

26 tháng 11 2021

ko biết

27 tháng 7 2021

a, \(2x\left(x+2\right)-\left(x+2\right)\left(x-2\right)=\left(x+2\right)^2=x^2+4x+4\)

b, \(\left(x-3\right)\left(x^2+3x+9\right)-\left(x^2-27x\right)=x^3-27-x^2+27x\)

c, \(\left(x+y\right)\left(x^2-xy+y^2\right)-\left(x-y\right)\left(x^2+xy+y^2\right)=x^3+y^3-x^3+y^3=2y^3\)

27 tháng 7 2021

2𝑥(𝑥+2)−(𝑥+2)(𝑥−2)

2𝑥^2+4𝑥−(𝑥+2)(𝑥−2)

2𝑥^2+4𝑥−(𝑥(𝑥−2)+2(𝑥−2))

2𝑥^2+4𝑥−(𝑥^2−2𝑥+2(𝑥−2))

2𝑥^2+4𝑥−(𝑥^2−2𝑥+2𝑥−4)

2𝑥^2+4𝑥−(𝑥^2−4)

2𝑥^2+4𝑥−𝑥^2+4

2𝑥^2−𝑥^2+4𝑥+4

25 tháng 9 2020

Rút gọn hả bạn ?

( 3x - 1 )2 - 9( x - 1 )( x + 1 )

= 9x2 - 6x + 1 - 9( x2 - 1 )

= 9x2 - 6x + 1 - 9x2 + 9

= 10 - 6x

( 2x + 3 )( 2x - 3 ) - ( 2x - 1 )2 - ( x - 1 )

= 4x2 - 9 - ( 4x2 - 4x + 1 ) - x + 1

= 4x2 - x - 8 - 4x2 + 4x - 1

= 3x - 9

2( x - 2y )( x + 2y ) + ( x - 2y )2 + ( x + 2y )2

= [ ( x + 2y ) + ( x - 2y ) ]2

= [ x + 2y + x - 2y ]2

= ( 2x )2 = 4x2

\(a)\)

\(21\left(x+3\right)^3:\left(3x+9\right)^2\)

\(=[21\left(x+3\right)^3]:[3^2\left(x+3\right)^2]\)

\(=7\left(x+3\right):3\)

Thay vào ta được: \(7.\frac{\left(-6+3\right)}{3}=7.\left(-3\right):3=-7\)

\(b)\)

Thay vào ta được:

\(\left(2.2^2-5.2+3\right)^4:[\left(2.2-3\right)^3:\left(2-1\right)^2]\)

\(=\left(2.4-10+3\right)^4:[\left(4-3\right)^31^2]\)

\(=1^4:\left(1^3.1\right)\)

\(=1:1\)

\(=1\)

\(c)\)

Thay vào ta được:

\(36.10^4.7^3:\left(-6.10^3.7^2\right)\)

\(=-6.10.7\)

\(=-420\)

19 tháng 9 2020

\(x^3-4x^2-9x+36=0\)

=> \(x^2\left(x-4\right)-9\left(x-4\right)=0\)

=> \(\left(x-4\right)\left(x^2-9\right)=0\)

=> \(\orbr{\begin{cases}x-4=0\\x^2-9=0\end{cases}}\Rightarrow\orbr{\begin{cases}x=4\\x=\pm3\end{cases}}\)

\(\left(x^2-9\right)^2-\left(x-3\right)^2=0\)

=> \(\left(x^2-9+x-3\right)\left[x^2-9-\left(x-3\right)\right]=0\)

=> \(\left(x^2+x-12\right)\left(x^2-9-x+3\right)=0\)

=> \(\left(x^2+x-12\right)\left(x^2-x-6\right)=0\)

=> \(\left(x^2-3x+4x-12\right)\left(x^2+2x-3x-6\right)=0\)

=> \(\left[x\left(x-3\right)+4\left(x-3\right)\right]\left[x\left(x+2\right)-3\left(x+2\right)\right]=0\)

=> \(\left(x-3\right)\left(x+4\right)\left(x-3\right)\left(x+2\right)=0\)

=> \(\left(x-3\right)^2\left(x+4\right)\left(x+2\right)=0\)

=> \(\hept{\begin{cases}\left(x-3\right)^2=0\\x+4=0\\x+2=0\end{cases}}\Rightarrow\hept{\begin{cases}x=3\\x=-4\\x=-2\end{cases}}\)

\(x^3-3x+2=0\)

=> \(x^3-x-2x+2=0\)

=> \(x^2\left(x-1\right)-2\left(x-1\right)=0\)

=> \(\left(x-1\right)\left(x^2-2\right)=0\)

=> x = 1